Enzyme stabilization by nano/microsized hybrid materials. Issue 1 (28th August 2012) - Hwang, Ee Taek; Gu, Man Bock
<x xml:space="preserve">Abstract</x> Immobilization is a key technology for successful realization of enzyme‐based industrial processes, particularly for production of green and sustainable energy or chemicals from biomass‐derived catalytic conversion. Different methods to immobilize enzymes are critically reviewed. In principle, enzymes are immobilized via three major routes (i) binding to a support, (ii) encapsulation or entrapment, or (iii) cross‐linking (carrier free). As a result, immobilizing enzymes on certain supports can enhance storage and operational stability. In addition, recent breakthroughs in nano and hybrid technology have made various materials more affordable hosts for enzyme immobilization. This review discusses different approaches to improve enzyme stability in various materials such as nanoparticles, nanofibers, mesoporous materials, sol–gel silica, and alginate‐based microspheres. The advantages of stabilized enzyme systems are from its simple separation and ease recovery for reuse, while maintaining activity and selectivity. This review also considers the latest studies conducted on different enzymes immobilized on various support materials with immense potential for biosensor, antibiotic production, food industry, biodiesel production, and bioremediation, because stabilized enzyme systems are expected to be environmental friendly, inexpensive, and easy to use for enzyme‐based industrial applications.